Suicidal thoughts in young people: Their frequency and relationships with personality factors - Stewart, M; Donaghey, C; Deary, I; Ebmeier, K (2008)
Suicide is one of the leading causes of death in adolescents and young people. This study aims to identify factors associated with suicidal thinking in young people. Levels of suicidal thinking in a large student population (n = 1039) were assessed using the GHQ-28; regression analysis identified personality (trait) and mood (state) correlates of suicidal thoughts. All volunteers were recruited from Universities in Edinburgh. Over 10% of students stated that they had suicidal thoughts within the last few weeks. Men scored slightly higher than women on suicidal thoughts. Variables relating to emotionality were the largest predictors of suicidal thoughts. Gender differences have also been reported in the relationship between self-rated mental health and suicide rates: males who had scored highly on the GHQ-28 had a higher suicide risk than females. Longitudinal studies in both men and women that assess personality predictors of self-harm and suicides are needed to control for confounders in non-randomised studies of suicide risk. © 2007 Elsevier Ltd. All rights reserved.